2005
DOI: 10.1098/rstb.2005.1726
|View full text |Cite
|
Sign up to set email alerts
|

An integrated approach to fast and informative morphological vouchering of nematodes for applications in molecular barcoding

Abstract: Molecular surveys of meiofaunal diversity face some interesting methodological challenges when it comes to interstitial nematodes from soils and sediments. Morphology-based surveys are greatly limited in processing speed, while barcoding approaches for nematodes are hampered by difficulties of matching sequence data with traditional taxonomy. Intermediate technology is needed to bridge the gap between both approaches. An example of such technology is video capture and editing microscopy, which consists of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(143 citation statements)
references
References 40 publications
2
139
0
2
Order By: Relevance
“…DNA barcoding has already been applied in many animals such as birds (Hebert et al 2004b), springtails invertebrates (Hogg and Hebert 2004), skipper butterflies (Hebert et al 2004a), blowflies (Whitworth et al 2007), leaf beetles (Jurado-Rivera et al 2009), nematodes (De Ley et al 2005), amphibians (Vences et al 2005a), ants (Smith et al 2005), crustaceans (Lefébure et al 2006), and scuttle flies (Boehme et al 2010). In addition, DNA barcodes have been obtained for more than 8000 species of fish and the COI sequences deposited in the Barcode of Life Data Systems (BOLD) online workbench and repository (Ragnasingham and Hebert 2007).…”
mentioning
confidence: 99%
“…DNA barcoding has already been applied in many animals such as birds (Hebert et al 2004b), springtails invertebrates (Hogg and Hebert 2004), skipper butterflies (Hebert et al 2004a), blowflies (Whitworth et al 2007), leaf beetles (Jurado-Rivera et al 2009), nematodes (De Ley et al 2005), amphibians (Vences et al 2005a), ants (Smith et al 2005), crustaceans (Lefébure et al 2006), and scuttle flies (Boehme et al 2010). In addition, DNA barcodes have been obtained for more than 8000 species of fish and the COI sequences deposited in the Barcode of Life Data Systems (BOLD) online workbench and repository (Ragnasingham and Hebert 2007).…”
mentioning
confidence: 99%
“…67 % in Pereira et al 2010). Earlier studies using the same fragment reported ''unreliable'' amplification results (Bhadury et al 2006a) as well as very high success rates (De Ley et al 2005). Due to the fact that a marker for molecular species identification should be easy to amplify, PCR optimization represents an essential task for further studies.…”
Section: Choice Of Marker and Implicationsmentioning
confidence: 99%
“…The primer pair D2A and D3B (De Ley et al 2005) was used for the amplification of the 28S rDNA: D2-D3 region. Amplicons were generated using PCR beads (illustra puReTaq Ready-To-Go PCR Beads, GE Healthcare UK Limited, Buckinghamshire, United Kingdom) in 25-ll reactions, filled up with 2 ll of DNA extract, 0.5 ll of primer D2A (20 pm/ll), 0.5 ll of primer D3B (20 pm/ll) and 22 ll of ddH 2 0.…”
Section: Pcr Performance and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations